2018
DOI: 10.4102/safp.v60i4.4907
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis in medical students at the University of the Free State

Abstract: Background: Allergic rhinitis, the most common form of chronic rhinitis, can adversely affect quality of life. The prevalence of allergic rhinitis in adolescents in South Africa has been estimated to be 38.5%, but there is a paucity of data from African countries on allergic rhinitis.Aim: The aim of this study was to determine the prevalence of allergic rhinitis in medical students in the Faculty of Health Science at the University of the Free State (UFS). Information was acquired on the effects that the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The findings of this current study showed that the prevalence of AR was 39.9% among the sample of 851 medical students from different regions of Saudi Arabia. Surprisingly, studies from other nations also reported very similar findings [5,[8][9][10]. However, there needs to be more studies in Saudi Arabia, where only one regional study was conducted in Jeddah and reported a prevalence of 16.7% among medical students [11].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The findings of this current study showed that the prevalence of AR was 39.9% among the sample of 851 medical students from different regions of Saudi Arabia. Surprisingly, studies from other nations also reported very similar findings [5,[8][9][10]. However, there needs to be more studies in Saudi Arabia, where only one regional study was conducted in Jeddah and reported a prevalence of 16.7% among medical students [11].…”
Section: Discussionmentioning
confidence: 89%
“…Data was gathered on the effects of the condition on participants in terms of symptoms, quality of life, disease management, and treatment. A prevalence of 39.1% was found, and sneezing, rhinorrhoea, and nasal obstruction were the most common and bothersome symptoms in those students [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in South African medical students found that allergic rhinitis affected their quality of life, with class attendance and participation in outdoor activities being affected [ 10 ]. Many participants reported that they frequently felt tired or miserable as a result of their nasal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Ketika diagnosis RA ditegakkan, pertanyaan apakah penderita RA juga menderita asma diperlukan, demikian halnya mengenai gejala atopi lainnya seperti alergi makanan dan eksema. Beberapa studi menyebutkan hampir 80% penderita asma juga menderita rinitis, dan 10%-40% penderita rinitis juga menderita asma (2,6,7) RA disebabkan oleh reaksi hipersensitifitas yang diperantarai oleh IgE (Reaksi tipe I Gel dan Coombs). Suatu alergen dikenali oleh Antigen Presenting Cell (APC) kemudian dipresentasikan kepada sel limfosit Th yang membutuhkan reseptor Human Leukosit Antigen (HLA).…”
Section: A Anamnesisunclassified